Предмет: Математика,
автор: Reaper655
Упростить в b3, с решением.
Приложения:
![](https://files.topotvet.com/i/bed/bed88b5179753e0d3021a87ef27c8fa7.jpg)
Ответы
Автор ответа:
1
Воспользуемся формулами приведения
cos(x-П)=-cosx
cos(3*П/2-x)=-sinx
sin(П-x)=xinx
cos(П/2+x)=-sinx
cos(x-П)*cos(3*П/2-x)/sin(П-x)*cos(П/2+x)=(-cosx)*(-sinx)/sinx*(-sinx)=
=(-cosx)/sinx=-ctqx
cos(x-П)=-cosx
cos(3*П/2-x)=-sinx
sin(П-x)=xinx
cos(П/2+x)=-sinx
cos(x-П)*cos(3*П/2-x)/sin(П-x)*cos(П/2+x)=(-cosx)*(-sinx)/sinx*(-sinx)=
=(-cosx)/sinx=-ctqx
Похожие вопросы
Предмет: Физика,
автор: Аноним
Предмет: Другие предметы,
автор: vikadasik
Предмет: Математика,
автор: Sasha55991
Предмет: Математика,
автор: renatabakaeva
Предмет: Литература,
автор: freefyu